A comparative study of production performance and animal health practices in organic and conventional dairy systems - Silva, Jenevaldo B. [UNESP]; Fagundes, Gisele M.; Soares, Joao P. G.; Fonseca, Adivaldo H.; Muir, James P. (Springer, 2014)
Health and production management strategies influence environmental impacts of dairies. The objective of this paper was to measure risk factors on health and production parameters on six organic and conventional bovine, caprine, and ovine dairy herds in southeastern Brazil over six consecutive years (2006-2011). The organic operations had lower milk production per animal (P a parts per thousand currency sign 0.05), lower calf mortality (P a parts per thousand currency sign 0.05), less incidence of mastitis (P a parts per thousand currency sign 0.05), fewer rates of spontaneous abortions (P a parts per thousand currency sign 0.05), and reduced ectoparasite loads (P a parts per thousand currency sign 0.05) compared to conventional herds and flocks. Organic herds, however, had greater prevalence of internal parasitism (P a parts per thousand currency sign 0.05) than conventional herds. In all management systems, calves, kids, and lambs had greater oocyte counts than adults. However, calves in the organic group showed lower prevalence of coccidiosis. In addition, animals in the organic system exhibited lower parasitic resistance to anthelmintics. Herd genetic potential, nutritive value of forage, feed intake, and pasture parasite loads, however, may have influenced productive and health parameters. Thus, although conventional herds showed greater milk production and less disease prevalence, future research might quantify the potential implications of these unreported factors.
Keywords: Brazil; Cattle; Goat; Milk production; Sheep; Sustainability